Pengukuran Kesiapan Pengguna Website Srikandi Menggunakan Metode TRI (Technology Readiness Index) - Jovita Vannia Harianja; Sisilia Thya Safitri; Laurens Manurung (Journal of Information System Research (JOSH), 2023)
The Srikandi website has been designated by the government as a general website for the Dynamic Archives Division. Srikandi's website is used to manage archives at Dinarpusda. This website was built to manage dynamic archives electronically which can have the effect of changing from manual to digital form and can help and facilitate employees in managing dynamic archives. The process of implementing information technology often creates new problems. The success of implementing information systems or technology adoption greatly influences user readiness. The purpose and benefits of this report are to fulfill the requirements for practical work courses. Distribution of questionnaires used to collect data. Questionnaires were distributed to the P3K division (Development, Development and Supervision of Archives) which was the sample in the study. The number of respondents was 15 respondents. Measuring user readiness for the Srikandi website uses the Technology Readiness Index (TRI) which functions to determine user readiness in using the Srikandi website in achieving the goal of making a website. The indicators used are optimism, innovation, discomfort and insecurity. The results of testing using TRI, obtained the results of the user's readiness level for the Srikandi website using belonging to the Medium category. This was obtained by looking at the results of the total TRI obtained, namely 3.03. This value is between 2.89 to 3.51 (2.90 ≤TRI≤3.51).